Analog Signal Processing Based on Silicon-Photonics and Its Application in Microwave Photonic Frontend - Minghua Chen; Hongchen Yu; Jingjing Wang; Hongwei Chen; Shizhong Xie (Dianxin kexue)
Signal processors are one of the significant elements in microwave photonic frontends，which determines the working ability of the entire system in many aspects.The silicon-photonics-based signal processors are especially attractive for their compact size and wonderful performance.The development of silicon-photonics-based signal processing for microwave photonic frontends was reviewed.